Exploring the Nexus between Political Risk and Financial Risk in the Balkan Countries: A Wavelet-Based NARDL Coherency analysis - Shuaibu, Sadat Momoh; Kirikkaleli, Dervis (Alanya Üniversitesi, 2022)
The empirical investigation of which risk factor—political or financial—is the optimal driver of country risk in emerging economies in the twenty-first century has grown into a significant and volatile issue in recent decades. This paper investigates the linkages between political risk and financial risk in four Balkan economies (i.e., Greece, Albania, Bulgaria, and Romania) from 1984 Q3 to 2018 Q4, using non-linear autoregressive distributed lag co-integration (NARDL) and wavelet coherence approaches. As a result, findings from the links between political risk and financial risk are being used to provide significant insights into effective urban planning in Balkan cities. The outcomes of the NARDAL analysis indicate that there are short-term and long-term asymmetric links between political risk and financial risk in the Balkan countries except for Romania. The wavelet coherence study also revealed that there is significant vulnerability between political risk and financial risk at different frequencies in the region, also, political risk is a key for predicting financial risk over the selected study period at different frequencies in Albania and Bulgaria.